Analysis of Different Investment Options Available for Tax Saving - Dr. Meghna Jain (HM Journals, 2023)
It is important to plan the taxation for every individual. An individual should plan income tax before the March end and this would help them in reducing their income tax which needs to be paid at the end of every financial year. This study is an attempt to understand the income tax slabs and the planning which an individual carries out before paying income tax. It is important for all the individuals to understand the different instruments available for tax saving so that they could plan in advance and do not end up paying a high amount of income tax. Planning tax is a very important aspect of financial planning. Tax when planned efficiently would enable the individuals to reduce their tax liability to minimum. In the research study, we have compared different tax saving investment options under ELSS i.e. HDFC tax saver direct plan, SBI long term equity fund, TATA India tax savings fund, under Fixed Deposit we have compared both Public and Private sector banks. Under public sector banks we have taken SBI, PNB & UNION bank, whereas under private sector we have taken AXIS, HDFC & ICICI bank. At last we have compared other options such as Public Provident Fund, Post Office Scheme & National Savings Certificate. T-test has been applied.